2021
DOI: 10.1038/s41598-021-01848-5
|View full text |Cite
|
Sign up to set email alerts
|

Muscle transcriptome provides the first insight into the dynamics of gene expression with progression of age in sheep

Abstract: The dynamic synergy of genes and pathways in muscles in relation to age affects the muscle characteristics. Investigating the temporal changes in gene expression will help illustrate the molecular mechanisms underlying muscle development. Here we report the gene expression changes in skeletal muscles through successive age groups in Bandur, a meat type sheep of India. RNA sequencing data was generated from the longissimus thoracis muscles from four age groups, ranging from lamb to adult. Analysis of 20 highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In addition to genes and pathways related to flight energy metabolic enzymes and flight muscle structural proteins as mentioned above, most other genes related to RNA metabolism, transport, redox, longevity, disease, and signaling pathway decreased with the increase in age. Muscle transcriptome in sheep showed genes related to muscle protein, phosphorylation, acetylation, metal binding and transport changed remarkably with aging, such as COX3, TPM2, MYL2, CYTB, ND4, TNNC and MYHT, their expression decreased with aging [ 22 ]. Homologous genes in S. frugiperda , such as AOB78_gp08 (COX3), AOB78_gp05 (ND4), AOB78_gp02 (CYTB), AOB78_gp12 (COX1), AOB78_gp11 (COX2), AOB78_gp04 (ND4L) and AOB78_gp09 (ATP6), also showed decreased expression with age ( Figure S5, Table S11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to genes and pathways related to flight energy metabolic enzymes and flight muscle structural proteins as mentioned above, most other genes related to RNA metabolism, transport, redox, longevity, disease, and signaling pathway decreased with the increase in age. Muscle transcriptome in sheep showed genes related to muscle protein, phosphorylation, acetylation, metal binding and transport changed remarkably with aging, such as COX3, TPM2, MYL2, CYTB, ND4, TNNC and MYHT, their expression decreased with aging [ 22 ]. Homologous genes in S. frugiperda , such as AOB78_gp08 (COX3), AOB78_gp05 (ND4), AOB78_gp02 (CYTB), AOB78_gp12 (COX1), AOB78_gp11 (COX2), AOB78_gp04 (ND4L) and AOB78_gp09 (ATP6), also showed decreased expression with age ( Figure S5, Table S11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome-based mapping trajectories of gene expression changes in different tissues of different organisms have provided deep insights into how biological functions change with age [ 19 , 20 ]. Studies in mammal skeletal muscle transcriptome have established a detailed framework of the global transcriptome and mRNA isoforms that govern muscle damage and homeostasis with age [ 21 , 22 ]. For example, specific mRNAs that changed significantly with age in human skeletal muscles were enriched for several aging-related processes, including cellular senescence, insulin signaling, myogenesis, oxidative phosphorylation and adipogenesis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional genomic tools have been widely used to study the molecular mechanisms of growth, development, and production traits in livestock ( 8 , 9 ). Transcriptome analysis has been used to identify the molecular information that regulates economically important traits of an organism.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on the muscle development of poultry embryos and post-hatching periods [ 17 , 18 ]. Previous studies have demonstrated differences in gene expression in sheep longissimus thoracic muscles during different stages [ 19 ], and some research has shown breed-specific expression profiles in sheep [ 20 ]. However, there is no comprehensive analysis of the dynamic changes of transcripts in skeletal muscle growth and development after birth and the differences between breeds.…”
Section: Introductionmentioning
confidence: 99%